PANCASILA DAN IDENTITAS KE-INDONESIA-AN: SEBUAH CATATAN KRISIS - Albintani, Muchid (Nakhoda: Jurnal Ilmu Pemerintahan, 2017)
The term there is no legislation under development of Pancasila as the basis of the state, but theposition of Pancasila is unshakeable. The anti-Pancasila attitude must also be anti-diversity that can live as a nation and a state [national crises]. Without affirmation or not in the legislation, Pancasila is the ?foundation and ideology of the state?. Based on the fact that there is irrelevant when the question arises, whether Pancasila is still needed as the basis of state and nation, or is Pancasila still needed as a source of national law that explicitly needs to be affirmed into the1945 Constitution and the sanctions of Pancasila tabulatively? This paper is an assertion of [reinforcement] of the Pencasila as an ideology into the 1945 Constitution or not, highly dependent on the winning electoral regime and the ?election-winning political party?. Pancasila as ?the foundation and ideology of the state? becomes the determinant of ?as close as the regime of the results of the practice of direct democracy?. Therefore, the affirmation of the essentials in building a lasting and harmonious life of fellow children of the nation in the future. Recognizing the reintroduction of the Indonesia?s identity of essence of Pancasila as the ideology of nation and state is based on ?national consensus?. This awareness is resilient, so that a country that has been established for more than 73 years does not experience an identity crisis.